قلق المستقبل لدى الطلبة الجامعيين و علاقته باتجاهاتهم نحو الزواج - حمداوي عامر; عاجب بومدين (My University, 2018)
Our study aimed at uncovering the relationship between the anxiety of the future and the trend toward marriage in a sample of students of the social sciences department at Ammar Thaliji University in Laghouat. The differences between the future anxiety and the trend toward marriage are determined according to the variables of gender and social status, Our sample consisted of (100) male and female students from the social sciences department who were chosen randomly, using the statistical package on social sciences SPSS 18, and the results of our study concluded That: 1-There is no statistically significant relationship between both the anxiety of the future and the trend toward marriage in our study sample. 2- There were no statistically significant differences in concern for the future due to gender in our study sample 3 - There are no statistically significant differences in future anxiety due to the social situation in our study sample. 4 - There are no significant differences in the trend towards marriage attributed to sex in our study sample. 5- There were no statistically significant differences in the trend towards marriage due to the social situation in our study sampleFuture Concern / Towards Marriage / University Students.